Canasta básica de alimentos recomendada para los hogares del Suroeste, antioqueño : Indicativo de los ingresos monetarios mínimos necesarios (2005)
ABSTRACT: To estabilsh the basic food groups recomended to families from the Southwest region of AntioquiaColombia Methodology Study design: Prevalence-descriptive study Subjects: represented by 7 towns, 14 small rural areas and 241 families living either in the urban and rural areas, using 95% confidence intervals. Methods: the basket of basic foods groups eaten by families was identified base on the information given by members of families about the food available during the week before the interview. We defined a basic diet, and a new caloric recomendations were calculated to improve some alimentary deficiencies. We stablished the minimum amount of money to the families of the region using the Engel’s coefficient Results: these families included all the food groups in their food pattern, but we found a little food variety. Sugars and cereals represent the 57% of the available energy. The basket of the basic food groups recommended improves the deficiencies founded in the availability of: milk, vegetables and fruits. Families need to get at least two times the in-come set up by the Colombian’s government in 2004 Conclusions: this study indicates all the neccesary changes that need to be done by the goverment, as increasing job opportunities, rising social and economic benefits, let people accessing at the basic food groups recomended in order to improve quality of life.